INTER-NOISE 79 - DOBRUCKI, Andrzej (Archives of Acoustics, 1980)
At plenary sessions 5 general papers and 54 poster – form papers were delivered. The other part of the debates took place in four parallel sections, including 22 invited papers and 86 contributed papers.Before the closing of the sessions, panel discussions were held, which summed up discussions in respective sections. Moreover, there was a special debate on the subject of training in the field of noise and vibration.Conference materials consisting of 944 pages were published in two-volume.